Pengaruh Konsentrasi dan Frekuensi Plant Growth Promoting Rhizobakteria (PGPR) terhadap Pertumbuhan dan Hasil Padi Merah (Oryza Nivara L.) - Kaet, Vinsensius Olin; Rusae, Aloysius; Kapitan, Origenes Boy (Savana Cendana, 2024)
This study aims to determine the concentration and frequency of watering the Plant Growht Promoting Rhizobacteria (PGPR) on the growth and yield of red rice (Oryza Nivara L.). This study revealed a factorial Randomized Block Design (RBD) consisting of two (2) factors with three (3) replications, the first factor (K) was the concentration of PGPR biological fertilizer consisting of control (K0), 50 g / 10 L ( K1), 75 g / 10 L (K2) the second factor (F) the frequency of fertilization consisting of 2 fertilization times (F1): planting time (WT) and 21 DAS, 4 fertilization times (F2): planting time (WT) 14 , 21, 42 DAS and 5 times fertilization (F3): planting time (WT) 14, 21, 42, and 56 DAS. Of these two factors, there are 9 treatment combinations, namely K0F1, K0F1, K2FI, K0F2, K1F2, K2F2, K0F3, K1F3, K2F3. The results showed that the PGPR concentration and frequency had an effect on the growth and yield of red rice plants, the growth parameters of rice plants, the concentration of 50 g / 10 L of water with a frequency of 4 times the best plant height (57.48 cm), 0.29 cm stem diameter tillers 23.33 chicks. root fresh weight (10.90 g), root dry weight (6.23 g), shoot fresh weight (87.53 g), shoot dry weight (36.16 g), number of panicles per clump (18.11 clumps), permalai pithy weight (5866.69 tonnes / ha). The combination treatment with a concentration of 50 g / 10 L of water with a frequency of 4 times PGPR watering is highly recommended because it can increase the growth and yield of red rice plants.